Efficacy comparison of immune combination therapies in subgroups for advanced hepatocellular carcinoma patients: Systematic review and network meta-analysis. - Yani Wang; Wanyee Lau; Yafei Li; Yichen Tian; Yongrong Lei; Feng Xia; Jianhua Wang (PLoS ONE, 2024)
Background There is a lack of precision in the immunotherapy strategy tailored for patients exhibiting diverse clinical characteristics. This study aims to employ a rigorous network meta-analysis (NMA) approach to systematically evaluate the effectiveness of immune-combination therapies among patients with advanced hepatocellular carcinoma, taking into account their varying clinico-characteristics. Methods Studies were retrieved from PubMed, Embase, Cochrane Library, and Web of Science databases. The included first-line phase III studies were categorized into three types: immunotherapy combined with anti-angiogenetic agents, immunotherapy combined with tyrosine kinase inhibitors, and dual immunotherapy, with sorafenib serving as the control group. The primary endpoint used to assess efficacy was overall survival (OS), facilitating a comparative analysis among the three treatment modalities. Furthermore, subgroup analyses were conducted to evaluate the varying effectiveness for patients with diverse clinico-characteristics. Secondary outcome measures included progression-free survival, objective response rate, and toxicity assessment. Results A total of 6 studies were included in the NMA, encompassing a cohort of 3840 patients. The results revealed that immunotherapy combined with anti-angiogenetic agents exhibited a significantly enhanced therapeutic effect in terms of improving OS compared to sorafenib (HR = 0.61, 95% CrI, 0.42-0.90). Furthermore, based on various clinicopathological features, this combination therapy demonstrated superior OS responses in specific patient subgroups: BCLC C (HR = 0.63, 95% CrI, 0.42-0.93), ECOG 1 (HR = 0.57, 95% CrI, 0.36-0.91), with extrahepatic spread (EHS) (HR = 0.59, 95% CrI, 0.37-0.92), alpha fetoprotein (AFP)<400ng/ml (HR = 0.56, 95% CrI, 0.33-0.94) and viral hepatitis positivity (HR = 0.56, 95% CrI, 0.39-0.77) (especially HBV (HR = 0.58, 95% CrI, 0.40-0.85)). Importantly, the advantage of this combination therapy was even more pronounced in patients with viral hepatitis positivity. Also, the adverse events associated with immunotherapy combined with antiangiogenic drugs were moderate. Conclusions Immunotherapy combined with anti-angiogenetic agents could represent the most effective first-line intervention for achieving improved OS, particularly in patients with viral hepatitis positivity.